Exploring under-utilized rose apple - Kishore, Kundan; Samant, Deepa; Singh, H S (Indian Horticulture, 2019)
Rose apple is an underutilized fruit crop grown in tropical regions of India, blessed with unique intrinsic texture, sugar:acid blend and rosy flavour which signify its high market potential. However, there is a need of research initiatives on crop improvement and shelf-life enhancement.